MARRIAGE LAW AND DIVORCE BASED ON ADAT LAW IN BALI - I Gusti Ayu Agung Ariani (Faculty of Law, Universitas Diponegoro, 2010)
Bali with the majority of its population embracing Hindu religion with patrilineai and caste system, in Marital law in force a national law Marriage Act No. 1174, which still allows the enforcement of the customary adat law. Those are of course influence the characteristic of the marriage and divorce, especially the type of marriage and the consequences of the status of wife and husband in marriage, right and obligation, authority over the children and properties. Furthermore, the status of wife I women if divorce take place, The women I wife as a widow is not automaticaliy return to her family of origin according to the type of marriage and the caste between husband and wife and many conditions must be fulfilled, if the conditions are not fulfilled, the divorced women will be trapped in uncertain and problematic status position, in which the man /male always get the benefit in all kind of ways